Community Context, Weapon Use, and Victim Injury: A Multi-Level Study of Offense Severity in the Sexual Victimization of Women - Dierenfeldt, Rick (American journal of criminal justice, 2019)
Prior studies of the sexual assault of women suggest the importance of weapon use, victim/offender familiarity, and offender intoxication as factors that contribute to offense severity in the form of victim injury. This body of literature is, however, inconsistent and limited insofar as it relies heavily on micro-level analysis of geographically limited samples of survivors and offenders. This study contributes to the literature through application of Agnew’s General Strain Theory and race-specific hierarchical generalized linear modeling to incident-level data from the National Incident-Based Reporting System in conjunction with contextual-level data from cities in which the incidents are nested. Our findings suggest weapon use, victim-offender familiarity, and offender intoxication each contribute to offense severity, but these relationships are conditioned by strain-inducing community characteristics.